Clinical and histopathologic features of canine tegumentary leishmaniasis and the molecular characterization of Leishmania braziliensis in dogs. - Jamile Lago; Juliana A Silva; Lairton Borja; Deborah B M Fraga; Albert Schriefer; Sergio Arruda; Ednaldo Lago; Edgar M Carvalho; Olívia Bacellar (Public Library of Science (PLoS), 2019)
Background Cutaneous leishmaniasis (CL), caused by Leishmania braziliensis, is the most important presentation of tegumentary leishmaniasis (TL) in Latin American. While the role of dogs as reservoirs of Leishmania infantum, and the clinic features of canine visceral leishmanisis are well described, little is known about the importance of dogs in the transmission of L. braziliensis to humans. In the present study, we determine the frequency of L. braziliensis infection in dogs with cutaneous and mucosal ulcers in an endemic area of CL. We also describe the clinical manifestations and histopathologic features, and determine if the parasites isolated from dogs are genetically similar to those found in humans. Methodology This is a cross sectional study in which 61 dogs living in an endemic area of CL and presenting ulcerated lesions were evaluated. Detection of L. braziliensis DNA by polymerase chain reaction (PCR) in skin biopsies, serology and leishmania skin test (LST) with soluble L. braziliensis antigen were performed. The clinical and histopathologic features were described, and we compared the genotypic characteristics of isolates obtained from dogs and humans. Principal findings The sensitivity of the three tests together to detect exposure was 89% and the concordance between the tests was high. The skin lesions were most frequent in the ears, followed by scrotal sac. The PCR was positive in 41 (67%) of animals, and the lesions in the snout, followed by the scrotal sac and ears were the sites where parasite DNA was most detected. There were genotype similarities between L.braziliensis isolates from dogs and humans. Conclusions The high frequency of L. braziliensis infection in dogs with ulcers and the similarities between the isolates of L. braziliensis and cutaneous leishmaniasis in dogs and humans in an endemic area of TL, raise the possibility of an important role of dogs in the transmission chain of L. braziliensis.